2013
DOI: 10.1159/000348879
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation and Plasticity

Abstract: Therapies for effective neurorehabiltiation are in part based on brain mechanism commonly described as neuroplasticity. These therapeutic approaches emphasize the re-learning of functionality that was lost due to the injury through reorganization of neural circuits in the remaining intact tissue. Important elements of these therapies are intensive and repetitive training, motivation and potentially interactive devices (therapy "robots") and supportive therapies such as brain stimulation or plasticity inducing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Previous studies on chronic stroke patients showed a significant decrease in shoulder and elbow motor impairment after the robot-assisted treatment [32,33] and different systematic reviews have explored the effects of intensive therapy on functional recovery [34,35], even if a consensus on this issue has not yet been reached, in particular as regards the effects on ADLs. Our previous experience on chronic stroke patients demonstrated that intensive robotic training can improve upper limb functional activity in terms of ROM and FM [36-38].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on chronic stroke patients showed a significant decrease in shoulder and elbow motor impairment after the robot-assisted treatment [32,33] and different systematic reviews have explored the effects of intensive therapy on functional recovery [34,35], even if a consensus on this issue has not yet been reached, in particular as regards the effects on ADLs. Our previous experience on chronic stroke patients demonstrated that intensive robotic training can improve upper limb functional activity in terms of ROM and FM [36-38].…”
Section: Discussionmentioning
confidence: 99%
“…Second, we aimed to investigate the functional correlates of language rehabilitation. We predicted that language therapy should be able to address brain plasticity, 32 promoting an early shift from RH to LH language-related areas in rehabilitated patients. Hence, early recruitment of LH perilesional areas would be the correlate of language improvement in early treated patients.…”
Section: Strokementioning
confidence: 99%
“…Some other studies also suggested that training devices which can provide rewarding schemes in a gaming environment had the ability to enhance the motivation of patients [ 44 , 45 ]. However, how to optimally apply motivational therapy into the rehabilitation to achieve better training outcomes is still unclear and need to be further investigated [ 46 ].…”
Section: Discussionmentioning
confidence: 99%